Identification and characterization of Pseudomonas syringae mutants altering the induction of type III secretion system - Deng, Xin (Kansas State University, 2009)
Pseudomonas syringae bacteria utilize the type III secretion system (T3SS) to deliver effector proteins into host cells. The T3SS and effector genes (together called the T3 genes hereafter) are repressed in nutrient rich medium but are rapidly induced after the bacteria are transferred into minimal medium (MM) or infiltrated into the plant. The induction of the T3 genes is mediated by HrpL, an alternative sigma factor that recognizes the conserved hrp box motif in the T3 gene promoters. The induction of hrpL is mediated by HrpR and HrpS, two homologous proteins that bind the hrpL promoter. To identify additional genes involved in regulation of the T3 genes, P. s. pv. phaseolicola (Psph) NPS3121 transposon insertion mutants were screened for reduced induction of avrPto-luc and hrpL-luc, reporter genes for promoters of effector gene avrPto and hrpL, respectively. Determination of the transposon-insertion sites led to the identification of genes with putative functions in signal transduction and transcriptional regulation, protein synthesis, and basic metabolism. A transcriptional regulator (AefRNPS3121) identified in the screen is homologous to AefR, a regulator of the quorum sensing signal and epiphytic (plant-associated) traits that was not known previously to regulate the T3 genes in P. s. pv. syringae (Psy) B728a. AefRNPS3121 in Psph NPS3121 and AefR in Psy B728a are similar in regulating the quorum sensing signal in liquid medium but different in regulating epiphytic traits such as swarming motility, entry into leaves, and survival on the leaf surface. The two component system RhpRS was identified in Pseudomonas syringae as a regulator of the T3 genes (Xiao et al. 2007). In the rhpS- mutant, the response regulator RhpR represses the induction of the T3 gene regulatory cascade, but induces its own promoter in a phosphorylation-dependent manner. Deletion and mutagenesis analyses revealed an inverted repeat (IR) element GTATC-N6-GATAC in the rhpR promoter that confers the RhpR-dependent induction. Computational search of the P. syringae genomes for the putative IR elements and Northern blot analysis of the genes with a putative IR element in the promoter region uncovered five genes that were upregulated (PSPTO2036, PSPTO2767, PSPTO3477, PSPTO3574, and PSPTO3660) and two genes that were down-regulated (PSPTO0536 and PSPTO0897) in an RhpR-dependent manner. ChIP assays indicated that RhpR binds the promoters containing a putative IR element but not the hrpR and hrpL promoters that do not have an IR element, suggesting that RhpR indirectly regulates the transcriptional cascade of hrpRS, hrpL, and the T3 genes. To identify additional genes involved in the rhpRS pathway, suppressor mutants were screened that restored the induction of the avrPto-luc reporter gene in the rhpS- mutant. Determination of the transposon-insertion sites led to the identification of rhpR, an ATP-dependent Lon protease, a sigma 70 family protein (PSPPH1909), and other metabolic genes. A lon- rhpS- double mutant exhibited phenotypes typical of a lon- mutant, suggesting that rhpS acts with or through lon. The expression of lon was elevated in rhpS- and other T3-deficient mutants, indicating a negative feedback mechanism. Both the lon- rhpS- and the PSPPH1909- rhpS- double mutant displayed enhanced transcription of hrpL in MM than did the rhpS- mutant.
Keywords: Pseudomonas syringae; Type III secretion system; Gene regulation; AefR; RhpRS; Biology, Genetics (0369)